2023
DOI: 10.1101/2023.09.11.557170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Of mice and men: Dendritic architecture differentiates human from mice neuronal networks

Lida Kanari,
Ying Shi,
Alexis Arnaudon
et al.

Abstract: The organizational principles that distinguish the human brain from those of other species have been a long-standing enigma in neuroscience. Here, we leverage advances in algebraic topology to uncover the structural properties of the human brain at subcellular resolution. First, we reveal a much higher perisomatic branching density in pyramidal neurons when comparing homologous cortical regions in humans and mice. Traditional scaling methods consistently fail to interpret this difference, suggesting a distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Previous studies observed high connectivity between neocortical layer 2-3 PNs in humans (10–15%; (Campagnola et al, 2022; Kanari et al, 2024; Peng et al, 2024, 2019; Planert et al, 2023; Seeman et al, 2018)). To validate that sparse synaptic connectivity in human CA3 resulted from circuit architecture, rather than tissue or recording quality, we performed additional multicellular recordings from human layer 2-3 neocortical neurons under identical experimental conditions, using temporal lobe tissue resected during hippocampal surgery ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies observed high connectivity between neocortical layer 2-3 PNs in humans (10–15%; (Campagnola et al, 2022; Kanari et al, 2024; Peng et al, 2024, 2019; Planert et al, 2023; Seeman et al, 2018)). To validate that sparse synaptic connectivity in human CA3 resulted from circuit architecture, rather than tissue or recording quality, we performed additional multicellular recordings from human layer 2-3 neocortical neurons under identical experimental conditions, using temporal lobe tissue resected during hippocampal surgery ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, not only does human CA3 employ much sparser connectivity than neocortical recurrent networks, but circuit architecture appears to sparsify across species with increasing brain size. Neocortical connectivity levels are comparable if not denser in humans than mice (Campagnola et al, 2022; Seeman et al, 2018), and formation of dense interconnectivity has been considered a mechanism for ‘uniquely human networks’ (Kanari et al, 2024). Our results suggest that the CA3 recurrent circuit uses a different mechanism to support human cognition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental research has demonstrated several ways in which neuronal connectivity is nonrandom with significant higher-order structure 30,33,42,43,45 . Moreover, small models with simple dynamics have shown the relevance of higher-order motifs in the observed activity [69][70][71] while in silico research has shown that the complexity is largely driven by neuronal morphologies 72,73,32 . At the same time, in the field of computational neuroscience, the bulk of research is conducted in models with simple connectivity based mostly on pairwise statistics that do not capture the entire complexity of the structure.…”
Section: Discussionmentioning
confidence: 99%

Key morphological features of human pyramidal neurons

Benavides-Piccione,
Blazquez-Llorca,
Kastanauskaite
et al. 2023
Preprint
Self Cite